Potent antimalarial activity of the alkaloid nitidine, isolated from a Kenyan herbal remedy - Gakunju, D M; Mberu, E K; Dossaji, S F; Gray, A I; Waigh, R D; Waterman, P G; Watkins, W M (Antimicrobial agents and chemotherapy, 1995)
Bioassay-guided fractionation of extracts of Toddalia asiatica, a plant used by the Pokot tribe of Kenya to treat fevers, has yielded the alkaloid nitidine as the major antimalarial component. Fractions containing nitidine have in vitro 50% inhibitory concentrations against Plasmodium falciparum in the range of 9 to 108 ng/ml for a range of chloroquine-susceptible and -resistant strains. The results show a lack of cross-resistance between chloroquine and nitidine.